2021
DOI: 10.1111/jpn.13512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physicochemical and structural properties of single and double feedstuffs derived from different botanic sources on in vitro starch digestion and glucose release kinetics

Abstract: Starch is the largest constituent in animal diets. The aims of this study were as follows:(a) to assess the variability of basic physicochemical properties and in vitro starch digestion of starchy feedstuffs and investigate relationship between physicochemical properties and starch digestion of the feedstuffs, and (b) to explore the effects of different sources of starchy feedstuffs on starch digestion and glucose release. In this study, we determined the inherent molecular structure and granular structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…In this experiment, the corn/cassava diet exhibited the highest peak glucose release rate after 15 min of in vitro digestion, followed by the corn/barley, corn, and corn/sorghum diets. These findings are consistent with the glucose release patterns observed for cassava, barley, corn, and sorghum in previous study [ 30 ]. However, following the peak glucose release rate, the corn/cassava diet dramatically decrease the glucose release rate, while the corn/sorghum diet more gradually decreased the glucose release rate.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this experiment, the corn/cassava diet exhibited the highest peak glucose release rate after 15 min of in vitro digestion, followed by the corn/barley, corn, and corn/sorghum diets. These findings are consistent with the glucose release patterns observed for cassava, barley, corn, and sorghum in previous study [ 30 ]. However, following the peak glucose release rate, the corn/cassava diet dramatically decrease the glucose release rate, while the corn/sorghum diet more gradually decreased the glucose release rate.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, accumulating evidence indicates that diets containing starch with different amylose/amylopectin ratios distinctly alter growth performance and nitrogen utilization [ 25 , 27 , 28 ], and these changes may be associated with the alterations in the kinetics of diet glucose release [ 6 , 29 ]. On the basis of our previous study on the effects of physicochemical and structural properties of single and double feedstuffs derived from different botanical sources on in vitro starch digestion and glucose release kinetics [ 30 ]. Four diets with different glucose release kinetics, containing similar levels of CP, NE, and starch, were formulated with starch sources from corn, corn/barley, corn/sorghum, or corn/cassava combinations in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there was no significant difference in feed intake among different NFD treatments, therefore, these differences in IEAA losses could partly be explained by the differences in starch digestion rate, the extent of starch digestion, or both. There are negative relationships between amylose content and starch digestion rate ( Zhong et al., 2021 ), and it has been observed that slowly digestible starch continuously supplies glucose, resulting in a gradual insulin release and leading to more efficient utilization of amino acid ( Weurding et al., 2001 ). Moreover, diets with a high AM/AP ratio have been found to reduce the consumption of AA by the intestinal epithelial cells, promoting more AA entry into the bloodstream to maintain protein synthesis, which has been reported in goats ( Lv et al., 2022 ), pigs ( van der Meulen et al., 1997 ), and chickens ( Selle and Liu, 2019 ; Yin et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%